Driving Sustainability in Power Generation: Amine Scrubbing Integration as a Cost-Effective Measure for Carbon Dioxide Mitigation - Nnadikwe Johnson; Onuoha fidelis wopara; Akuchie Justine Chukwuma; Stephen Oyelami (Jurnal Teknik Indonesia, 2026)
The imperative of energy security, sustainability, and independence necessitates the continued use of coal for electricity generation. However, to mitigate rising CO2 levels, developing carbon capture and storage (CCS) technologies is crucial. This study explores various approaches to optimize CO2 capture using chemical solvents, focusing on reducing the energy demands of solvent regeneration. Our analysis reveals that the current cost of CO2 capture stands at approximately #55,000.000 (Naira) per ton of CO2 , with a target to reduce it to below #25,000.000,00 (Naira) per ton of CO2 . We evaluate the technical and economic performance of different approaches, calculating the specific cost per ton of CO2  captured. Our results show that:- Current Cost: #55,000.000,00 (Naira) per ton of CO2 - Target Cost: Below #25,000.000,00 (Naira) per ton of CO2 - Efficiency Reduction: Minor efficiency reductions observed in some proposed schemes